Henri Cernuschi biography - Cernuschi, Henri, 1821-1896.
Biography of Henri (Enrico) Cernuschi.
Typewritten transcript.
Economist and banker.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bankers; Economists